2016
DOI: 10.1093/bfgp/elw023
|View full text |Cite
|
Sign up to set email alerts
|

MECP2, a multi-talented modulator of chromatin architecture

Abstract: It has been a long trip from 1992, the year of the discovery of MECP2, to the present day. What is surprising is that some of the pivotal roles of MeCP2 were already postulated at that time, such as repression of inappropriate expression from repetitive elements and the regulation of pericentric heterochromatin condensation. However, MeCP2 performs many more functions. MeCP2 is a reader of epigenetic information contained in methylated (and hydroxymethylated) DNA, moving from the 'classical' CpG doublet to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 119 publications
(185 reference statements)
2
69
0
1
Order By: Relevance
“…As an example, it has been described that the Methyl-CpG-Binding Domain Protein 1 (MBD1) suppresses the expression of FGF-2 promoting differentiation during adult neurogenesis in the hippocampus [52]. MECP2 encodes an epigenetic factor that influences chromatin structure and considered to act mainly as a transcriptional repressor [53]. Furthermore, recent studies using induced pluripotent stem cells derived from Rett patients (a disorder causes generally by point mutations on the MECP2 gene) demonstrated the role of the MeCP2 protein in neuronal maturation [54].…”
Section: Main Textmentioning
confidence: 99%
“…As an example, it has been described that the Methyl-CpG-Binding Domain Protein 1 (MBD1) suppresses the expression of FGF-2 promoting differentiation during adult neurogenesis in the hippocampus [52]. MECP2 encodes an epigenetic factor that influences chromatin structure and considered to act mainly as a transcriptional repressor [53]. Furthermore, recent studies using induced pluripotent stem cells derived from Rett patients (a disorder causes generally by point mutations on the MECP2 gene) demonstrated the role of the MeCP2 protein in neuronal maturation [54].…”
Section: Main Textmentioning
confidence: 99%
“…Deletion of Mecp2 in mice causes mechanosensory dysfunction as well as social interaction deficits . MeCP2 is a reader of epigenetic information and is a modulator of chromatin architecture . Recent studies found that 17 out of 37 MeCP2‐binding proteins were splicing factors, and that MeCP2 regulated mRNA splicing through interacting with 5hmC and epigenetic changes in histone markers, and such interaction and epigenetic changes lead mainly to effects in synaptic functions and mRNA splicing .…”
Section: Epigenetics Of Autismmentioning
confidence: 99%
“…64 MeCP2 is a reader of epigenetic information and is a modulator of chromatin architecture. 65 Recent studies found that 17 out of 37 MeCP2-binding proteins were splicing factors, and that MeCP2 regulated mRNA splicing through interacting with 5hmC and epigenetic changes in histone markers, and such interaction and epigenetic changes lead mainly to effects in synaptic functions and mRNA splicing. 66 This is consistent with the finding of misregulation of Serine/ Arginine Repetitive Matrix 4 -nSR100-dependent splicing in more than one-third of the brains of autistic patients.…”
Section: Mecp2 Mutationmentioning
confidence: 99%
“…DNA methylation at the promoter region of the genes usually represses gene expression 10 . Methyl‐CpG‐binding domain family proteins are the readers of DNA methylation; these proteins are often associated with gene repression, which would recruit other remodelers, enzymes to the methylated DNA 11 . As a member of this family, methyl‐CpG‐binding protein 2 (MeCP2) selectively binds with methyl‐CpG residues and was thought to be a transcriptional repressor 12 .…”
Section: Introductionmentioning
confidence: 99%